ŻYCIE UKRYTE W SŁOWIE. "BEKSIŃSCY. PORTRET PODWÓJNY" MAGDALENY GRZEBIAŁKOWSKIEJ W ŚWIETLE POSTSTRUKTURALIZMU - cl, redakcja (Colloquia Litteraria, 2020)
Life Hidden in Words. Magdalena Grzebiałkowska's "Beksińscy. Portret podwójny" and Poststructuralism The article analyzes Magdalena Grzebiałkowska's biographical "Beksińscy. Portret podwójny" which focuses on the lives of Zdzisław Beksiński and Tomasz Beksiński. The author looks at the construction of the biography and its relationship to poststructuralism, which allows for an appreciation of the literary features of the book. He points to how the specificity of the content, language, a mode of narration in Grzebiałkowska's book make it a full-fledged literary work itself. As such the book departs from a typical biographical scheme. Juxtaposing the book with poststructural ideas leads to the reconsideration of the role of the author in the process of shaping of a biographical narrative.